Analisis Makna Lafadz Sulthan dalam Al-Qur'an: Studi Perspektif Semantik / Analysis of the Meaning of Lafadz Sulthan in the Qur'an from the Perspective of Semantic Studies - Rahmat Linur; Mahyudin Ritonga Ritonga; Julhadi Julhadi (Jurusan Bahasa dan Sastra Arab Universitas Islam Negeri Alauddin Makassar, 2022)
The term “Sulthan” is one of the Musytarak words (words with several meanings) found in the Qur'an. The term